Inside Augustine - Pranger, Marinus B. (Augustinian studies, 2016)
This article, which is an adaptation of a lecture delivered at Villanova University in the Fall of 2015, proposes a reading of Augustine’s Confessions (conf.) with the assistance of the notions of absorption and theatricality. The very use of those notions is meant to counterbalance the readings generated by our overfamiliarity with Augustinian interiority. By replacing interiority with a concept that, heretofore, is alien to the Augustinian vocabulary, it becomes possible to block facile access to mystical interpretations of conf. on the one hand, and to embark upon the (admittedly challenging) task of reassessing the nature of "confessing" on the other. This new reading demonstrates the difficulties involved in approaching the confessor fully involved in his act of sustained confessing. A comparison is also made with the notion of absorption in the visual arts. Just as spectatordom becomes problematic vis-à-vis a painting whose personae look inward rather than outward, so too the position of the reader vis-à-vis a text whose confessing creator uninterruptedly addresses his Confessee demands a redefinition of the reader’s role and place in the process.